Simultaneous 18-FDG PET and MR imaging in lower extremity arterial disease - Koppara, Tobias; Dregely, Isabel; Nekolla, Stephan G.; Nährig, Jörg; Langwieser, Nicolas; Bradaric, Christian; Ganter, Carl; Laugwitz, Karl-Ludwig; Schwaiger, Markus; Ibrahim, Tareq (Frontiers in Cardiovascular Medicine, 2024)
Background: Simultaneous positron emission tomography (PET) and magnetic resonance imaging (MRI) is a novel hybrid imaging method integrating the advances of morphological tissue characterization of MRI with the pathophysiological insights of PET applications.Aim: This study evaluated simultaneous 18-FDG PET/MR imaging in lower extremity arterial disease (LEAD) for the characterization of atherosclerotic lesions.Methods: Simultaneously acquired 18-FDG PET and contrast enhanced MRI were performed in eight patients with symptomatic stenoses of the superficial femoral artery (SFA) in an integrated whole-body PET/MRI scanner. Intravascular imaging using optical coherence tomography of the SFA was applied for invasive plaque characterization. Histology of plaque specimens was performed after directional atherectomy.Results: MRI showed contrast enhancement at the level of the arterial stenosis assessed on T2w-and T1-w images as compared to a control area of the contralateral SFA (0.38 ± 0.15 cm vs. 0.23 ± 0.11 cm; 1.77 ± 0.19 vs. 1.57 ± 0.15; p-value <0.05). On PET imaging, uptake of 18F-FDG (target-to-background ratio TBR > 1) at the level of the symptomatic stenosis was observed in all but one patient. Contrast media induced MR signal enhancement was detected in all plaques whereas FDG-uptake in PET imaging was increased in lesions with active fibroatheroma and reduced in fibro-calcified lesions.In this multimodal imaging study, we report the feasibility and challenges of simultaneous PET/MR imaging of LEAD which might offer new perspectives for risk estimation.